Management of Islamic Boarding School Curriculum Integration in Improving the Quality of Madrasah Education: Manajemen Integrasi Kurikulum Pesantren Dalam Meningkatkan Mutu Pendidikan Madrasah - Islam, M. (Halaqa: Islamic Education Journal, 2021)
The integration of the pesantren curriculum in formal educational institutions has not been widely carried out. Although there are partial characteristics and have not been managed properly. The integrated management of the pesantren curriculum in madrasah can be used as an alternative in strengthening the uniqueness of madrasas, especially religious material. The results of this study indicate that the integration of the pesantren curriculum into madrasah can improve understanding of religious material more thoroughly and deeply. Classical book studies, which have been disinterested by young people, can be revitalized through the integration of the pesantren curriculum in madrasas. For that, it is necessary to plan, organize, implement, and evaluate carefully to implement integrated management of the pesantren curriculum in the madrasah curriculum. Structurally, the curriculum can be included in local content.